I-kiyohkātoyāhk (we visit): adapting nēhiyawēwin/nīhithawīwin (Cree) language learning to the COVID-19 reality. (December 2020) - McIvor, Onowa; Sterzuk, Andrea; Cook, William
I-kiyohkātoyāhk (we visit) is a phrase which describes our experience of trying to recreate an online version of our way of life, being together in the language. The following report is our view of the ways nēhiyawēwin/nīhithawīwin (Cree) language learning has adapted to the COVID-19 reality since March 2020. Our hope is that by sharing the experience most familiar to us, the one we are living as learners and speaker-teacher, we offer a useful perspective and potential solutions or directions for others.